A Transformative Era: The Roberts Court, Constitutional Interpretation, and Public Administration. Issue 6 (July 2020) - Newbold, Stephanie P.
The Constitutional School of American Public Administration dictates that the rule of law serves as the intellectual and practical foundation of the field. One way to support the Constitutional School is to examine how the U.S. Supreme Court works to shape the administrative state in its own image. This article provides a thorough examination for how the Court under Chief Justice John Roberts constitutionally protected laws affecting gay marriage, affirmative action, abortion rights, gun ownership, and health care while simultaneously narrowed constitutional protections concerning voting rights, campaign finance laws, and employer mandated contraceptive coverage. These contrasting constitutional viewpoints not only represent a transformative era in the history of the nation's highest Court but also in how public administrative agencies implement the Court's decisions.